The BRICS Order: Assertive or Complementing the West? - Isaac Khambule (Journal of BRICS Studies)
Book review: Monyae, D and Ndzendze, B. (eds.) 2021: The BRICS Order: Assertive or Complementing the West? Palgrave MacMillan, 364 Pages, ISSN 2662-2483 ISSN 2662-2491 (electronic) International Political Economy Series ISBN 978-3-030-62764-5 ISBN 978-3-030-62765-2 (eBook)